The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.amjhyper.2005.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Capacity and 24-h Blood Pressure in Prehypertensive Men and Women

Abstract: Background:Prehypertensive individuals are at increased risk for developing hypertension and cardiovascular disease compared to those with normal blood pressure (BP). Physically active, normotensive individuals are also at lower risk for developing hypertension than sedentary individuals. We assessed the relationship between fitness and 24-h ambulatory BP in prehypertensive men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 39 publications
2
24
0
2
Order By: Relevance
“…It has been postulated that the microvasculature of the brain is particularly vulnerable to the excessive fluctuations in BP, 28 as a consequence of vascular dysfunction 15 and poor CV fitness. 10 The current investigation revealed that higher DBP response to a submaximal exercise test in midlife was associated with smaller brain volume in later life. This evidence complements previous studies supporting the association between exaggerated exercise BP and target organ damage 16,32 or CV events.…”
Section: 31mentioning
confidence: 93%
See 1 more Smart Citation
“…It has been postulated that the microvasculature of the brain is particularly vulnerable to the excessive fluctuations in BP, 28 as a consequence of vascular dysfunction 15 and poor CV fitness. 10 The current investigation revealed that higher DBP response to a submaximal exercise test in midlife was associated with smaller brain volume in later life. This evidence complements previous studies supporting the association between exaggerated exercise BP and target organ damage 16,32 or CV events.…”
Section: 31mentioning
confidence: 93%
“…Higher CV fitness may also reduce the impact of vascular risk factors 9,10 that are associated with brain structural abnormalities and cognitive decline. 11,12 Poor CV fitness and vascular dysfunction exaggerate fluctuations in blood pressure (BP) and heart rate (HR) during lowlevel exercise.…”
mentioning
confidence: 99%
“…Moderate and high-fit prehypertensive individuals exhibit significantly lower ambulatory BP, 11 exercise BP, and heart rate (HR) at submaximal and absolute workloads 12 when compared with unfit. We also reported significantly lower exercise BP at the absolute submaximal workloads of 3 to 6 METs 13 and LVM 14 in hypertensive patients after 16 weeks of low-to-moderate intensity exercise training.…”
mentioning
confidence: 99%
“…The level of decreased coronary risk attributable to regular physical activity is similar to that of other lifestyle factors such as avoiding cigarette smoking or Mediterranean diet. The risk of CVD (including CHD and stroke) or CHD alone is significantly reduced in more physically active or fitter persons, with a relative risk reduction nearly twice as great for cardiorespiratory fitness (CFR) than for physical activity increase at all percentiles (Kokkinos et al, 2006, Kokkinos et al, 2016. A possible explanation for the stronger dose-response gradient for fitness than for physical activity is that fitness is measured objectively, whereas physical activity is assessed by self-reports and questionnaires that may lead to misclassification and bias towards finding weaker physical activity or health benefit associations (Moore et al, 2012).…”
Section: Sedentary Lifestylementioning
confidence: 99%